Analisis Sektor Unggul Dalam Penunjang Perekonomian di Kabupaten Berau Tahun 2010-2019 - Rifki Khoirudin (Jurnal Darma Agung, 2022)
The research has the objective of having a superior zone in Berau Regency and being in a location close to the Berau Regency government to increase the zone that has the energy that regulates the level of economic development in Berau Regency. The results of the Location Quotient (LQ) analysis obtained from the 2010-2019 average can be recognized that those categorized into the base zone in Berau Regency are the zones which include the zones of Agriculture, Forestry, and Fisheries, Mining and Quarrying, Water Supply, Waste Management. , Recycled Waste, Wholesale and Retail Trade; Repair of Cars and Motorbikes, Transportation and Warehousing, Provision of Dining and Drinking Accommodations, Real Estate, Learning Services, Health Services and Social Activities, and other services. The zone is categorized in the base zone because it has an LQ ≥ 1 value. As well as the results of the analysis of Shift Share (SS), the basis of the zone that has competitive energy is the mining and quarrying, wholesale and retail zones; Car and Motorcycle Repair, Transportation and Warehousing, Real Estate, Health Services and Social Activities. Researchers apply to the Berau Regency government to prioritize the development of zones categorized on a zone basis and have great information to support the economy of Berau Regency